Attitudes of school teachers toward influenza and COVID-19 vaccine in Greece during the COVID-19 pandemic. Issue 10 (3rd October 2021) - Gkentzi, Despoina; Benetatou, Eleni; Karatza, Ageliki; Kanellopoulou, Aimilia; Fouzas, Sotirios; Lagadinou, Maria; Marangos, Markos; Dimitriou, Gabriel
ABSTRACT: Our study aims to assess the attitudes, knowledge, and influenza vaccine uptake of school teachers, the intention to uptake influenza vaccine as well as the COVID-19 vaccine and to identify factors associated with vaccine acceptance during the COVID-19 pandemic in Greece. A cross-sectional online survey was conducted among elementary and kindergarten school teachers in the area of Western Greece from June 2020 to August 2020. A self-administered questionnaire was distributed via an internet-based link along with an invitation e-mail. Responses from 399 participants were retrieved. 139 (34.8%) had received the annual influenza vaccine in the season 2019–2020, whereas 215 (53.9%) stated that they would get it in the forthcoming season 2020–2021 ( p < .001). 152 (38.1%) intent to get the COVID-19 vaccine when available. For COVID-19 vaccine factors that were independently associated with the intention to uptake included more than 15 years at work ( p = .001), prior influenza vaccine uptake ( p = .003), believing that COVID-19 vaccine should be mandatory ( p = .04) and that school teachers are a high-risk group for COVID-19 ( p = .001). In conclusion, COVID-19 pandemic appeared to have an impact on the intention of school teachers to get vaccinated for influenza. The low level of COVID-19 vaccine acceptance intention among the teachers in our cohort warrants further attention. Public health interventions should aim to increase knowledge on both influenza and COVID-19 and prevention of them via immunization in this particular at-risk population.